2019
DOI: 10.1101/717090
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular and genetic regulation of pig pancreatic islet cell development

Abstract: Reliance on rodents for understanding pancreatic genetics, developmental biology and islet function could limit progress in developing interventions for human diseases like diabetes mellitus.Similarities of pancreas morphology and function, and pancreatic disease modeling in pigs suggest that porcine and human pancreas developmental biology may have useful homologies.However, little is known about pig pancreas development. To fill this knowledge gap, we investigated fetal and neonatal pig pancreas at multiple,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 101 publications
0
15
0
Order By: Relevance
“…A wealth of data are available about the embryonic development of pancreas in mammals, 23,24 but less is known about the postnatal development of this organ. We procured 2 1-day-old samples (Supplementary Table 3) and performed sNuc-seq (10,528 nuclei) (Figure 5A and B).…”
Section: Single-nucleus Sequencing Of the Human Neonatal Pancreasmentioning
confidence: 99%
“…A wealth of data are available about the embryonic development of pancreas in mammals, 23,24 but less is known about the postnatal development of this organ. We procured 2 1-day-old samples (Supplementary Table 3) and performed sNuc-seq (10,528 nuclei) (Figure 5A and B).…”
Section: Single-nucleus Sequencing Of the Human Neonatal Pancreasmentioning
confidence: 99%
“…104 However, recently, Dpp4 mRNA and DPP4 protein have been proposed to be expressed dynamically in late fetal stages of β-cell development, which coincide with the expression of GLP-1R and may regulate GLP-1-mediated signaling responses important for β-cell maturation. 105 The importance of preproglucagon-derived peptides in the control of islet cell communication through cAMP has been recently demonstrated, 106,107 and the addition of sitagliptin to metformin is associated with a lower rate of diabetes progression. 108 These data suggest that although an islet-DPP4-GLP-1 axis may not regulate whole-body glucose metabolism, it may regulate necessary islet-specific signaling important in β-cell function and survival.…”
Section: Role Of Islet-derived Dpp4 In Glycemic Regulationmentioning
confidence: 99%
“…In many aspects, such as islet size distribution, anatomy and vascularization, the proportion of beta cells in the islets and the spatial arrangement and interaction of the endocrine cell types, porcine islets are more similar to human islets than to mouse islets (Dufrane et al 2005;Hoang et al 2014). In line with these observations, RNA sequencing studies revealed that porcine and human beta and alpha cells share characteristic molecular and developmental features not observed in the corresponding mouse cells (Kim et al 2019). Transgenic pigs expressing fluorescent reporter genes in the beta cells (Kemter et al 2017;Matsunari et al 2014) will help to improve the resolution of such analyses to the single-cell level.…”
Section: Introductionmentioning
confidence: 67%